2021
DOI: 10.1186/s12943-021-01394-8
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circIKBKB promotes breast cancer bone metastasis through sustaining NF-κB/bone remodeling factors signaling

Abstract: Background Breast cancer (BC) has a marked tendency to spread to the bone, resulting in significant skeletal complications and mortality. Recently, circular RNAs (circRNAs) have been reported to contribute to cancer initiation and progression. However, the function and mechanism of circRNAs in BC bone metastasis (BC-BM) remain largely unknown. Methods Bone-metastatic circRNAs were screened using circRNAs deep sequencing and validated using in situ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 41 publications
1
42
0
Order By: Relevance
“…The statistical analysis of the results of qRT-PCR of clinical samples also showed a negative correlation between the expression of circ-MTHFD1L and miR-615-3p in PDAC tissues. The abnormal expression of miR-615-3p has been confirmed to be related to the occurrence and development of gastric cancer, breast cancer, and non-small cell lung cancer [ 15 17 ]. However, there are no reports about it and pancreatic cancer globally.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The statistical analysis of the results of qRT-PCR of clinical samples also showed a negative correlation between the expression of circ-MTHFD1L and miR-615-3p in PDAC tissues. The abnormal expression of miR-615-3p has been confirmed to be related to the occurrence and development of gastric cancer, breast cancer, and non-small cell lung cancer [ 15 17 ]. However, there are no reports about it and pancreatic cancer globally.…”
Section: Discussionmentioning
confidence: 99%
“…The unique circular structure of circRNAs gives them inherent resistance to exonuclease degradation and is more stable than linear RNA [ 13 ]. In recent years, extensive studies have found that circRNAs play a key role in tumorigenesis by acting as competing endogenous RNAs, such as liver cancer [ 14 ], lung cancer [ 15 ], Gastric cancer [ 16 ], breast cancer [ 17 ]. Therefore, circRNAs have great potential as a valuable tumor diagnostic biomarker or therapeutic target [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Immune checkpoints (ICPs)- and immunogenic cell death modulators (ICDs)-related genes were obtained from the previous studies[ 7 , 22 ]. Then the expression level of ICPs and ICDs were compared among different immune subtypes by Pairwise t-tests[ 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…Tumor antigen with or without adjuvant is the main component of a typical cancer vaccine, assisting immune cells in recognizing and eliminating cancer cells [ 7 ]. The advantages were minimal non-specific effect, non-toxic, long-term immune memory and wide treatment window for tumor vaccine treatment which could overcome the limits of drug resistance, high costs, limited therapeutic effects and other possible adverse reactions associated with traditional immunotherapy and chemotherapy [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…CircRNAs can bind directly to RBPs to form RNA-protein complexes to regulate RBPs and further affect the expression and biology of downstream proteins ( Huang et al, 2020 ; Feng J. et al, 2021 ; Chen J. et al, 2021 ; Xu et al, 2021 ). Muscleblind-like (MBL) binds to exon 2 of its parental gene and induces cyclization to form circMbl, which also binds to MBL to reduce MBL abundance, thereby reducing circMbl production ( Ashwal-Fluss et al, 2014 ).…”
Section: Acts As a Competitive Endogenous Rnamentioning
confidence: 99%